Structural studies of phosphorylation-dependent interactions between the V2R receptor and arrestin-2 - He, Qing-Tao; Xiao, Peng; Huang, Shen-Ming; Jia, Ying-Li; Zhu, Zhong-Liang; Lin, Jing-Yu; Yang, Fan; Tao, Xiao-Na; Zhao, Ru-Jia; Gao, Feng-Yuan; Niu, Xiao-Gang; Xiao, Kun-Hong; et al. (Nature communications, 2021)
Arrestins recognize different receptor phosphorylation patterns and convert this information to selective arrestin functions to expand the functional diversity of the G protein-coupled receptor (GPCR) superfamilies. However, the principles governing arrestin-phospho-receptor interactions, as well as the contribution of each single phospho-interaction to selective arrestin structural and functional states, are undefined. Here, we determined the crystal structures of arrestin2 in complex with four different phosphopeptides derived from the vasopressin receptor-2 (V2R) C-tail. A comparison of these four crystal structures with previously solved Arrestin2 structures demonstrated that a single phospho-interaction change results in measurable conformational changes at remote sites in the complex. This conformational bias introduced by specific phosphorylation patterns was further inspected by FRET and 1 H NMR spectrum analysis facilitated via genetic code expansion. Moreover, an interdependent phospho-binding mechanism of phospho-receptor-arrestin interactions between different phospho-interaction sites was unexpectedly revealed. Taken together, our results provide evidence showing that phospho-interaction changes at different arrestin sites can elicit changes in affinity and structural states at remote sites, which correlate with selective arrestin functions. The interaction between a GPCR, such as the vasopressin receptor-2 (V2R), and arrestin depends on the receptors’ phosphorylation pattern. Here authors use FRET and NMR to analyze the phosphorylation patterns of the V2R-arrestin complex and show that phospho-interactions are the key determinants of selective arrestin conformational states and correlated functions.